1990
DOI: 10.1038/bjc.1990.90
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-type plasminogen activator in plasma from breast cancer patients determined by enzyme-linked immunosorbent assay

Abstract: Summary An enzyme-linked immunosorbent assay (ELISA) using monoclonal and polyclonal antibodies against t-PA was used to measure the concentration of tissue-type plasminogen activator (t-PA) in plasma from 34 healthy donors and 92 breast cancer patients with a varying extent of disease. The mean value of t-PA in plasma for the healthy donors was 2.4 ± 2.1 ng ml'-(s.d.). The mean value for the breast cancer patients was 5.3 ± 4.3 ng ml '. This increase was statistically significant at the 1% level. There was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Both uPA and PAI-1 are established prognostic factors in several types of cancer, a high tissue level of both components generally being associated with tumour progression and with poor disease-free and/or overall survival (reviewed by Duffy, 1996;Schmitt et al, 1997). Furthermore, several investigators have reported on the potential diagnostic and prognostic relevance of tPA analysed either in plasma or in tumour tissues from patients, including those afflicted with breast or colon cancer (Layer et al, 1987;De Bruin et al, 1988;Duffy et al, 1988;Needham et al, 1988;Grøndahl-Hansen et al, 1990;Jänicke et al, 1990Jänicke et al, , 1991Rella, et al, 1993;Yamashita et al, 1993Yamashita et al, , 1995Duggan et al, 1997). In addition, some studies even have examined the presence of complexes between tPA and PAI-1 in plasma from healthy individuals and patients with various diseases (Niwano et al, 1992;Hansson et al, 1994;Maser et al, 1997).…”
mentioning
confidence: 99%
“…Both uPA and PAI-1 are established prognostic factors in several types of cancer, a high tissue level of both components generally being associated with tumour progression and with poor disease-free and/or overall survival (reviewed by Duffy, 1996;Schmitt et al, 1997). Furthermore, several investigators have reported on the potential diagnostic and prognostic relevance of tPA analysed either in plasma or in tumour tissues from patients, including those afflicted with breast or colon cancer (Layer et al, 1987;De Bruin et al, 1988;Duffy et al, 1988;Needham et al, 1988;Grøndahl-Hansen et al, 1990;Jänicke et al, 1990Jänicke et al, , 1991Rella, et al, 1993;Yamashita et al, 1993Yamashita et al, , 1995Duggan et al, 1997). In addition, some studies even have examined the presence of complexes between tPA and PAI-1 in plasma from healthy individuals and patients with various diseases (Niwano et al, 1992;Hansson et al, 1994;Maser et al, 1997).…”
mentioning
confidence: 99%
“…Breast cancer patients with tumors with a high t-PA content had a better prognosis than those with low t-PA [Duffy et al, 1988]. In any case, the mean plasma levels of t-PA have been found to be higher in breast cancer patients than in healthy donors [Grondahl-Hansen et al, 1990;Mannucci et al, 1990], with a positive correlation between the mean t-PA plasma concentration and extent of the disease. In a subset of patients participating in the trial, we investigated the effects of 4-HPR on circulating PA levels.…”
Section: Plasminogen Activatormentioning
confidence: 84%
“…Neuroimmunomodulatory function of sero= tonin (5-HT) has been demonstrated [3,4]. It was shown that activation of serotoninergic mechanisms in the central nervous system is accompanied by suppression of the immune system mediated through pituitary-adrenal regulatory mechanisms.…”
Section: Effect Of Antiserotonin Antibodies On Functionalmentioning
confidence: 99%
“…These cells also possess urokinase receptors (URR). Urokinase is primarily associated with cells, and only low UR concentration is present in the plasma [4]. Expression of URR dramatically increases in arterial lesions, atheromas, and atherosclerotie plaques [8,10].…”
mentioning
confidence: 99%